Розвиток кадрового потенціалу державної служби України в умовах сучасних змін - Чертюк Ольга Вячеславівна (My University, 2023)
Обґрунтовано напрями розвитку кадрового потенціалу державної служби України в умовах сучасних змін та розроблено практичні рекомендації щодо стратегування в цій сфері, а саме: виявлено тенденції реформування державного управління в Україні у період з 2013 року по теперішній час та необхідність впровадження змін в систему державної служби; визначено сутність феномену “кадровий потенціал державної служби” та узагальнено сучасні підходи до розвитку кадрового потенціалу державної служби, зокрема європейську, американську та східну моделі; здійснено аналіз стану кадрового потенціалу державної служби України із застосуванням методу експертного оцінювання. А також розроблено рекомендації щодо стратегування у сфері розвитку кадрового потенціалу державної служби України (сприяння розвитку професійної мобільності державних службовців та поширення методу кадрового профайлингу в систему управління персоналом в органах публічної влади). Ключові слова: професіоналізація, кадровий потенціал, державна служба, розвиток кадрового потенціалу.

The directions for the development of the personnel potential of the civil service of Ukraine in the conditions of modern changes were substantiated and practical recommendations for strategizing in this area were developed, namely: the trends of public administration reform in Ukraine in the period from 2013 to the present and the need to implement changes in the civil service system were identified; the essence of the phenomenon "staff potential of the civil service" is defined and modern approaches to the development of the personnel potential of the civil service are summarized, in particular the European, American and Eastern models; an analysis of the state of the personnel potential of the civil service of Ukraine was carried out using the method of expert evaluation. Recommendations were also developed for strategizing in the field of development of personnel potential of the civil service of Ukraine (promoting the development of professional mobility of civil servants and spreading the method of personnel profiling in the personnel management system in public authorities). Key words: professionalization, personnel potential, public service, development of personnel potential.
Development of human resources civil service of Ukraine in the context of modern changes